The Sense of Education Within the Achagua and Piapoco Communities - Bolaños Motta, José Ignacio; Daza Monras, Yamile Andrea; Rivera Barrios, Kendy Viviana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This work is the result of a research project carried out in public schools in the Achagua and Piapoco indigenous communities, located in the municipality of Puerto López in Meta. The approach seeks to explore the sense of education implemented in public education, in contrast to that one of adulthood developed by schoolchildren belonging to the mentioned indigenous reservations. This exploratory study of an ethnographic nature was aimed at identifying the reasons for the high-school dropout among students living in the reservation through the use of data collection strategies such as interviews and social cartography. Based on the collected information, a series of emerging categories was established on the basis of the ideas of the mestizo education and other western or artificial perspectives that enter into relationship with a group of communities having a tendency to be westernized due to the lack of an intercultural school and as a consequence of the strong influence of the Protestant churches, the new companies in the area and public school.